Breast cancer risk, worry, and anxiety: Effect on patient perceptions of false-positive screening results. (April 2020) - Lee, Janie M.; Lowry, Kathryn P.; Cott Chubiz, Jessica E.; Swan, J. Shannon; Motazedi, Tina; Halpern, Elkan F.; Tosteson, Anna N.A.; Gazelle, G. Scott; Donelan, Karen
Abstract: Objective: The impact of mammography screening recall on quality-of-life (QOL) has been studied in women at average risk for breast cancer, but it is unknown whether these effects differ by breast cancer risk level. We used a vignette-based survey to evaluate how women across the spectrum of breast cancer risk perceive the experience of screening recall. Methods: Women participating in mammography or breast MRI screening were recruited to complete a vignette-based survey. Using a numerical rating scale (0–100), women rated QOL for hypothetical scenarios of screening recall, both before and after benign results were known. Lifetime breast cancer risk was calculated using Gail and BRCAPRO risk models. Risk perception, trait anxiety, and breast cancer worry were assessed using validated instruments. Results: The final study cohort included 162 women at low (n = 43, 26%), intermediate (n = 66, 41%), and high-risk (n = 53, 33%). Actual breast cancer risk was not a predictor of QOL for any of the presented scenarios. Across all risk levels, QOL ratings were significantly lower for the period during diagnostic uncertainty compared to after benign results were known (p < 0.05). In multivariable regression analyses, breast cancer worry was a significant predictor of decreased QoL for all screening scenarios while awaiting results, including scenarios with non-invasive imaging alone or with biopsy. High trait anxiety and family history predicted lower QOL scores after receipt of benign test results (p < 0.05). Conclusions: Women with high trait anxiety and family history may particularly benefit from discussions about the risk of recall when choosing a screening regimen. Highlights: Impact of screening recall on quality-of-life does not vary by breast cancer risk. Breast cancer worry predicts lower quality-of-life ratings while awaiting results. Quality-of-life ratings improve after receipt of benign results. High trait anxiety predicts lower quality-of-life after benign results are known.